Unravelling the secrets of blazar OT 081: a multiwavelength investigation. Issue 4 (20th March 2023) - Deng, Junhao; Jiang, Yunguo
ABSTRACT: OT 081 is a low-synchrotron-peaked (LSP) frequency blazar target, and has strong emission in the γ-ray band. In July 2016, a significant short-term flare was observed in the optical, X-ray and γ-ray bands. In addition, a long-term orphan flare was observed in the X-ray band from 2009 to 2012. Using the multiwavelength data, we investigate the origin of these two flares and the emission mechanism of γ-ray photons. According to the correlation analysis, we suggest that both flares may have originated from the formation of the new dissipation zones within the jet rather than the change of Doppler factor. The 2016 short-term flare happens on small-scale dissipation zone, while the long-term X-ray flare originates from large scale dissipation zone. Furthermore, we study the spectral energy distribution (SED) to investigate whether the broad-line region (BLR) and the dust torus can provide enough external photons to explain the γ-ray emission of the 2016 flare within the leptonic scenario. We find that the 2016 flare can be explained when the scale of the newly formed dissipation zone is comparable to that of BLR. For the 2009–2012 orphan X-ray flare, we suggest that it may be dominated by the synchrotron self-Compton (SSC) process in a newly formed dissipation zone at pc scale, since both the magnetic field and the external soft photon field energy density are small enough at this region. In summary, the emission mechanism of OT 081 could be explained in the leptonic scenario.